The primary prevention of epilepsy: A report of the Prevention Task Force of the International League Against Epilepsy - Thurman, D; Begley, C; Carpio, A; Helmers, S; Hesdorffer, D; Mu, J; Touré, K; Parko, K; Newton, C (Wiley, 2018)
Among the causes of epilepsy are several that are currently preventable. In this review, we summarize the public health burden of epilepsy arising from such causes and suggest priorities for primary epilepsy prevention. We conducted a systematic review of published epidemiologic studies of epilepsy of 4 preventable etiologic categories—perinatal insults, traumatic brain injury (TBI), central nervous system (CNS) infection, and stroke. Applying consistent criteria, we assessed the quality of each study and extracted data on measures of risk from those with adequate quality ratings, summarizing findings across studies as medians and interquartile ranges. Among higher‐quality population‐based studies, the median prevalence of active epilepsy across all ages was 11.1 per 1000 population in lower‐ and middle‐income countries (LMIC) and 7.0 per 1000 in high‐income countries (HIC). Perinatal brain insults were the largest attributable fraction of preventable etiologies in children, with median estimated fractions of 17% in LMIC and 15% in HIC. Stroke was the most common preventable etiology among older adults with epilepsy, both in LMIC and in HIC, accounting for half or more of all new onset cases. TBI was the attributed cause in nearly 5% of epilepsy cases in HIC and LMIC. CNS infections were a more common attributed cause in LMIC, accounting for about 5% of all epilepsy cases. Among some rural LMIC communities, the median proportion of epilepsy cases attributable to endemic neurocysticercosis was 34%. A large proportion of the overall public health burden of epilepsy is attributable to preventable causes. The attributable fraction for perinatal causes, infections, TBI, and stroke in sum reaches nearly 25% in both LMIC and HIC. Public health interventions addressing maternal and child health care, immunizations, public sanitation, brain injury prevention, and stroke prevention have the potential to significantly reduce the burden of epilepsy.